1970
DOI: 10.1113/jphysiol.1970.sp009029
|View full text |Cite
|
Sign up to set email alerts
|

Bicarbonate secretion and non‐Na component of the short‐circuit current in the isolated colonic mucosa of Bufo arenarum

Abstract: SUMMARY1. In the isolated colonic mucosa ofBufo arenarum, under special circumstances, there is a variable fraction of the short-circuit current (0-38 %) that is unaccounted for by either the Na or the Cl and bicarbonate transmembrane net fluxes.2. The hypothesis that a special kind of bicarbonate transport may account for the non-Na component of the short-circuit current was investigated. According to this, bicarbonate ions formed within the membrane await transport towards the mucosal solution within a compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1970
1970
2014
2014

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…For simplicity, the models assume a single barrier to transport from lumen (L) to blood (B). In all likelihood, the H and HCO3 ions are produced by intracellular hydration of CO2 (Carlinsky & Lew, 1970) which is consistent with the high levels of carbonic anhydrase in colonic mucosa (Carter & Parsons, 1971). All values are expressed in pequiv/cm2 .…”
Section: Discussionsupporting
confidence: 72%
“…For simplicity, the models assume a single barrier to transport from lumen (L) to blood (B). In all likelihood, the H and HCO3 ions are produced by intracellular hydration of CO2 (Carlinsky & Lew, 1970) which is consistent with the high levels of carbonic anhydrase in colonic mucosa (Carter & Parsons, 1971). All values are expressed in pequiv/cm2 .…”
Section: Discussionsupporting
confidence: 72%
“…The lack of complete identity between the total I~c and net Na absorption has been a consistent observation studies of the amphibian colon [-3, 5, 6, 7, 20]. Carlinsky and Lew [3] suggested that the nonsodium portion of the I~ in the colon of Bufo arenarum was due to HCO 3 secretion from an intra- …”
Section: Na Fluxes and The Source Of The Short-circuit Currentmentioning
confidence: 83%
“…If the Na ions that are actively transported towards the serosal surface come from an intracellular compartment that exchanges slowly with the Na ions present in the mucosal solution, the rate at which isotope enters the serosal solution will underestimate the true mucosa-toserosa Na flux since the Na is coming from a Na pool that has not yet reached the specific activity of the Na in the mucosal solution, but is slowly approaching it. However, this situation can be ruled out for the following reason: 1 cm2 of membrane has an average wet weight of about 23 mg (Carlisky & Lew, 1970); the superficial layer of epithelial cells, which are the only cells involved in the active processes discussed here, contribute not more than 10 % of the total weight of the membrane. If the intracellular concentration of Na is supposed to be 65 m-equiv/kg and if the Na is equally distributed among the different types of cell, the total amount of Na inside the epithelial cells of 1 cm2 526 V. L. LEW IONIC FLUXES IN ISOLATED TOAD COLON of membrane is 0 13 ,t-equiv.…”
Section: Discussionmentioning
confidence: 94%